EFEKTIVITAS PENJUALAN BUKU MELALUI SALURAN DISTRIBUSI TIDAK LANGSUNG - Novita Rosanti (Jurnal Bisnis dan Kewirausahaan, 2016)
This study aims to determine the effectiveness of book sales through indirect distribution channels. The data used in this research is secondary data with data collection techniques through documentation and interviews. The analytical method used is quantitative descriptive realization that compares with sales targets. The results showed that the sale of books via indirect distribution channels has been effective.